2017
DOI: 10.1016/j.jcorpfin.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Do tax havens create firm value?

Abstract: International audienceOn October 11, 2011, a non-governmental organization called ActionAid published a report condemning the FTSE 100 firms for holding an unusually large number of subsidiaries in tax havens. Urging the government to implement appropriate actions, the report raised the firms' costs of holding tax haven subsidiaries. After this event, the stock prices of the nonfinancial firms experienced a 0.9% abnormal drop (corresponding to about £ 9 billion in market capitalization). Those better-governed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…On October 11, 2011, ActionAid released a report titled “Addicted to Tax Havens,” which received widespread attention and was the subject of general interest, many popular press articles, and parliamentary discussion. Choy, Lai, and Ng [] document significant negative returns for FTSE 100 firms on this date, consistent with market participants anticipating negative consequences from the unwanted publicity. We examine whether the negative returns for FTSE 100 firms around the October 11, 2011 event date are especially concentrated in firms that did not disclose their full subsidiary list in 2006.…”
Section: Additional Testsmentioning
confidence: 67%
See 2 more Smart Citations
“…On October 11, 2011, ActionAid released a report titled “Addicted to Tax Havens,” which received widespread attention and was the subject of general interest, many popular press articles, and parliamentary discussion. Choy, Lai, and Ng [] document significant negative returns for FTSE 100 firms on this date, consistent with market participants anticipating negative consequences from the unwanted publicity. We examine whether the negative returns for FTSE 100 firms around the October 11, 2011 event date are especially concentrated in firms that did not disclose their full subsidiary list in 2006.…”
Section: Additional Testsmentioning
confidence: 67%
“…Including all U.K. firms in the regression implies that the intercept term captures the market return for FTSE 100 firms that were initially compliant as well as all other The dependent variable is the Three-Day Buy-and-Hold Return Centered on ActionAid Report Date, October 11, 2011. This report is the focus of Choy, Lai, and Ng [2014]. Incomplete Subs List is an indicator variable equal to one for FTSE 100 firms that did not disclose the full list of their subsidiaries prior to the 2010 public pressure related to subsidiary disclosure and equal to zero, otherwise.…”
Section: Returns Analysis Around Actionaid's Report On Tax Haven Usagementioning
confidence: 99%
See 1 more Smart Citation
“…Tax havens can help firms lower their corporate taxes by enabling them to book a greater share of profits in these havens through mechanisms such as transfer pricing, intra firm loans, and royalty payments (Gravelle, ). This opportunity to substantially lower taxes by using tax havens, as suggested by economic theory, would mean a positive stockholder return to the use of tax havens (Choy, Lai, & Ng, , ). The secrecy afforded by tax havens on the other hand can encourage those in control of the firm, that is, managers and controlling stockholders, to act opportunistically against the interests of other stockholders and thereby lower stockholder returns.…”
Section: Background Literaturementioning
confidence: 99%
“…The limited empirical evidence to date in the literature suggests the use of tax havens by advanced economy firms yield positive stockholder returns, and these returns are greater for firms with better firm‐level corporate governance. For example, based on a sample of UK firms, specifically the FTSE 100 firms, Choy et al (, ) found the average firm in their sample had a stockholder value gain of at least 0.9% associated with their tax haven use and such stockholder gains were greater for firms with better firm‐level corporate governance.…”
Section: Background Literaturementioning
confidence: 99%